2020
DOI: 10.1155/2020/6525826
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum β-Lactamase (ESBL) Genotypes among Multidrug-Resistant Uropathogenic Escherichia coli Clinical Isolates from a Teaching Hospital of Nepal

Abstract: Urinary tract infections (UTI) represent the most common bacterial infections among patients visiting outpatient clinics of healthcare centers in Nepal. However, treatment of such infections is compounded by emergence and spread of multidrug-resistant uropathogens associated with extended-spectrum β-lactamases (ESBLs). In this study, we aimed to investigate the burden of antimicrobial resistance and occurrence of ESBL genes among clinical isolates of uropathogenic Escherichia coli at a tertiary care teaching h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 33 publications
(57 reference statements)
10
48
3
2
Order By: Relevance
“…In this study, more than one-fourth (27.3%) of the total E. coli isolates were confirmed as ESBL producers. This finding is consistent with the previous studies reported from Model Hospital, Bagbazar, Kathmandu [15], Everest Hospital, Baneshwor, Kathmandu [20], and International Friendship Hospital, Maharajgunj, Kathmandu [3], and lower than a study reported from Manmohan Memorial Medical College and Teaching Hospital (MMCTH) [16,18] and Om Hospital and Research Centre, Kathmandu [41]. The higher rate of ESBL in this organism compared to the previous studies may indicate the temporal impact of increasing infections and AMR over the years.…”
Section: Esbl Producers and Acquisition Of Resistant Genotypessupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, more than one-fourth (27.3%) of the total E. coli isolates were confirmed as ESBL producers. This finding is consistent with the previous studies reported from Model Hospital, Bagbazar, Kathmandu [15], Everest Hospital, Baneshwor, Kathmandu [20], and International Friendship Hospital, Maharajgunj, Kathmandu [3], and lower than a study reported from Manmohan Memorial Medical College and Teaching Hospital (MMCTH) [16,18] and Om Hospital and Research Centre, Kathmandu [41]. The higher rate of ESBL in this organism compared to the previous studies may indicate the temporal impact of increasing infections and AMR over the years.…”
Section: Esbl Producers and Acquisition Of Resistant Genotypessupporting
confidence: 93%
“…PCR amplification reactions were carried out in a 21 µL volume, in which a master mix containing 200 µM of dNTP s (dATP, dCTP, dGTP, and dTTP), 120 nM of each primer (forward and reverse), 0.5 U/µL of Taq polymerase in 1× PCR buffer, 25 mM of MgCl 2 , and 3 µL of DNA template was added. Amplification reactions were performed in a DNA thermal cycler under the following thermal and cycling conditions for the bla TEM (F.P:5′-GAGACAATAACCCTGGTAAAT-3′R.P:5′-AGAAGTAAGTTGGCAGCAGTG-3′) [ 16 ] and bla CTX-M (Forward Primer: 5′-TTTGCGATGTGCAGTACCAGTAA-3′, Reverse Primer: 5′-CGATATCGTTGGTGGTGCCATA-3′) [ 31 ] genes: initial denaturation at 94 °C for 1 min, denaturation at 95 °C for 5 min of 35 cycles, annealing at 55 °C for 1 min of 35 cycles for bla CTX-M and 56 °C for 45 s of 35 cycles for bla TEM , extension at 72 °C for 1 min of 35 cycles, and final extension at 72 °C for 10 min [ 16 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are encoded by genes that are often located on transferable conjugative plasmids. Additionally, genes that confer resistance to antibacterial agents, other than beta-lactams, are frequently carried simultaneously on these plasmids and contribute to the dissemination of resistance [3] .…”
Section: Introductionmentioning
confidence: 99%